A Curious Case of Hemolytic Anemia with Pseudoreticulopenia. (21st April 2022) - Mayer, Scott; Srinivasan, Nikhilesh; Nguyen, Jenny; Spilman, Ryan; Scherbak, Dmitriy
Abstract : Herein, we present a unique case of a Coombs-negative, steroid-refractory autoimmune hemolytic anemia (AIHA) complicated by pseudoreticulopenia, describe its clinical presentation, histopathologic findings, and management, and review the salient literature. Coombs-negative, steroid-refractory AIHAs represent fewer than 1% of all AIHAs. Diagnosis of the disease is difficult and often delayed due to the pursuit of alternate diagnoses following a negative Coombs test. However, when suspicion remains high for an autoimmune process, the super-Coombs test may be utilized for the diagnosis of AIHA that the traditional Coombs test fails to detect. A majority of cases respond to rituximab as the indicated second-line therapy, but delays in diagnosis and subsequent treatment may increase morbidity. Reticulopenia may be associated with AIHAs secondary to bone marrow dysfunction, but this patient had a normal function marrow confirmed on biopsy. Indeed, reticulopenia in this case was a diagnostic conundrum that further obscured the diagnosis and delayed treatment. Ultimately, reticulopenia was determined to be pseudoreticulopenia secondary to an alteration in the maturation of the erythroid lineage due to an independent, newly diagnosed pernicious anemia. The interaction of these multiple coexisting disease processes is not previously described in the literature. Increased physician awareness of steroid-refractory, Coombs-negative AIHA, and the development of pseudoreticulopenia as a laboratory finding in pernicious anemia may help to improve patient outcomes.